Chironomidae (Diptera: Insecta) of Alaska, USA, with descriptions of new species and a checklist - Namayandeh, Armin; Hudson, Patrick L.; Bogan, Daniel L.; Hudson, John P. (Zootaxa, 2024)
The current study results from the collection of Chironomidae, which began in 1994 and continued until the present time in six biogeographical regions of Alaska, USA. We established that 427 species are currently reported from Alaska, adding 154 new faunistic records and six new species. In this study, we described Chaetocladius (Chaetocladius) kimfrangosi sp. nov., Chaetocladius (Chaetocladius) mendenhallensis sp. nov., Chaetocladius (Chaetocladius) tonitrus sp. nov., Corynoneura palus sp. nov., Stilocladius keithsomersi sp. nov., and Paratanytarsus giminilacus sp. nov.. Additionally, we describe the larva of a pupa Roback (1971) thought likely to belong to Krenopelopia narda Roback, 1971, the female of Cricotopus (Paratrichocladius) scaturigineus (Makarchenko & Makarchenko, 2014), and the female and pupa of Heleniella parva Sæther, 1985. For the first time, we provided a checklist of Chironomidae with distributional records from Alaska.